The reliability and validity of the 3- minute critical power test in linear and isokinetic mode - Wright, J.; Jobson, S.; Bruce-Low, S.; Jessop, D. (Journal of Science and Cycling, 2015)
Background: Exercise testing for cyclists provides key information when setting training and race strategies. Shorter testing protocols are favored by coaches and recently it has been suggested that critical power (CP) and the finite work capacity, W', can be estimated from a single 3-minute bout of 'all-out' exercise using the Lode Excalibur Sport cycle ergometer. These estimates are termed end power (EP) and work above end power (WEP) respectively (Vanhatalo et al., 2007: Medicine & Science in Sports & Exercise, 39(3), 548-55). Considering the physiological basis of this test, it should be possible to accurately estimate CP and W' irrespective of the ergometer used. However, a recent study (Karsten et al., 2013: International Journal of Sports Medicine, 35(4), 304-9) has suggested that although reliable, the 3-minute test in isokinetic mode using an SRM ergometer does not provide a valid measure of CP or W'.